Human Diversity : The Biology of Gender, Race, and Class - Murray, Charles (New York Twelve, 2020)
All people are equal but, as Human Diversity explores, all groups of people are not the same -- a fascinating investigation of the genetics and neuroscience of human differences.
Include Index, References and Graphs
Keywords: Sociobiology